1973
DOI: 10.1051/lait:1973525-52614
|View full text |Cite
|
Sign up to set email alerts
|

Influence des souches seules et associées de L. bulgaricus et Str. Thermophilus ainsi que des traitements du lait sur la production d'aldéhyde acétique dans le yaourt

Abstract: Le yaourt, dans sa zone d'origine qui est la péninsule balkanique, était préparé avec du lait de chèvre et à l'aide de cultures naturelles. Les recherches de Grigoroff [1] et de Kuntze [2], conduites au début de ce siècle, ainsi que les recherches successives de Orla-Jensen [3], nous ont indiqué que les ferments lactiques de telles cultures étaient représentés par Lactobacillus jugurti et Lactobacillus bulgaricus. Cependant Metchnikoff indiqua que le produit original était principalement obtenu avec des lactob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Acetaldehyde is a reactive, low molecular weight, flavor active compound found in a variety of foods and beverages such as cheese (Weerkamp, Klijn, Neeter, & Smit, 1996), yogurt (Bottazzi, Battistotti, & Montescani, 1973), beer (Margalith, 1981) and wine (Bottazzi et al, 1973;Dittrich & Barth, 1984;Margalith, 1981;Weerkamp et al, 1996). It is quantitatively the most important carbonyl compound produced during alcoholic fermentations (AF) with final concentrations typically varying between 10 and 200 mg l − 1 (McCloskey & Mahaney, 1981), and a sensory threshold from 100 to 125 mg l − 1 in wine for free acetaldehyde (Zoecklein, Fugelsang, Gump, & Nury, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Acetaldehyde is a reactive, low molecular weight, flavor active compound found in a variety of foods and beverages such as cheese (Weerkamp, Klijn, Neeter, & Smit, 1996), yogurt (Bottazzi, Battistotti, & Montescani, 1973), beer (Margalith, 1981) and wine (Bottazzi et al, 1973;Dittrich & Barth, 1984;Margalith, 1981;Weerkamp et al, 1996). It is quantitatively the most important carbonyl compound produced during alcoholic fermentations (AF) with final concentrations typically varying between 10 and 200 mg l − 1 (McCloskey & Mahaney, 1981), and a sensory threshold from 100 to 125 mg l − 1 in wine for free acetaldehyde (Zoecklein, Fugelsang, Gump, & Nury, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to produce flavour compounds is widespread among the lactic acid bacteria. Keenan etal(1966), Bottazzi and Dellaglio (1967), Bottazzi and Vescovo (1969), and Bottazzi et al (1973) have shown that strains of Streptococcus thermophilus and Lactobacillus delbrueckii subsp bulgaricus produce different amounts of carbonyl compounds, in particular acetaldehyde, when grown in skimmed cow's milk. Substances that contribute to f1avour are particularly significant in the preparation of natural yoghurt.…”
Section: Introductionmentioning
confidence: 99%
“…bulgaricus for the manufacture of yoghurt. When both bacteria gain a mutual benefit, this association is known as proto-cooperation (57), and it often results in higher acidification rates (2,7,8,25,46,50), a lower final pH (46,53), a more abundant S. thermophilus population (10,46,53), stimulation of aromatic compound production (10,15,24,30), improved stability of the final product (24), and an increase of exopolysaccharide production (11) compared to monocultures. This cooperation effect improves the yield of fermentation and is therefore of industrial interest.…”
mentioning
confidence: 99%
“…In turn, S. thermophilus stimulates the growth of L. delbrueckii subsp. bulgaricus by the production of formic acid under anaerobic conditions (10,64) and of carbon dioxide (22). Carbon dioxide results from the decarboxylation of urea catalyzed by urease, present and widely distributed only in S. thermophilus among LAB, which are generally recognized as safe (36,47).…”
mentioning
confidence: 99%